A Retrospective Study on Mesenteric Venous Thrombosis in a Referral Hospital in East Africa - Wismayer, Richard (New Frontiers in Medicine and Medical Research Vol. 15, 2021)
Introduction: Acute mesenteric venous thrombosis is a rare condition with the most common site of thrombosis development being the superior mesenteric vein. Patients predisposed to this condition tend to develop a disruption to Virchow’s triad of endothelial injury, stasis and hypercoagulability. In the acute form the presentation is with bowel ischaemia and so a diagnosis before bowel gangrene develops remains a challenge. The limited experience with this condition in the East African region shows that a delayed diagnosis due to limited investigative capacity results in patients’ experiencing acute renal failure and a high mortality. Therefore the objective of this paper was to describe the presentation and management of four patients with mesenteric venous thrombosis in a Referral Hospital in East Africa, followed by a review on the aetiology, clinical features and management of this condition. Methods: A descriptive retrospective review of four patients over an 18-month period. Demographic and clinical data was extracted from the patients’ clinical files and manual analysis using a spreadsheet was performed. Results: Over an 18-month period, four patients were reported. All patients had a delay in diagnosis with acute symptoms persisting for 5 days up to 21 days. Two patients died within 30-days post-operatively of complications which included short bowel syndrome and acute kidney failure. Two patients survived developing complications from short bowel syndrome and another the complications of acute kidney injury requiring haemodialysis. Conclusions: A delay in diagnosis of acute MVT characterises this short case series. This resulted in all cases presenting with gangrenous bowel and hence the high mortality. Venous clot propagation is prevented with anticoagulation which is associated with decreased mortality and recurrence. Thrombolysis and thrombectomy should be considered in certain circumstances to prevent bowel of questionable viability. In the last four decades the mortality from MVT has decreased and currently stands at 10-20% however there is no sufficient literature in East Africa to make this judgement.